Increasing Quality of Crackers Productivity as a Food Commodity in Jember Regency - Sholihin, Muhammad Rijalus; Rizki, Via Lailatur; Maidah, Firdaus Al (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
The COVID-19 pandemic has greatly impacted all sectors, including small and medium-sized businesses such as cracker producers and resellers. The problems faced in the midst of the pandemic include manual production processes, lack of management skills, monotonous and less innovative products, and difficulties in marketing. In this activity, there are three partners, namely UD. Sumber Rejeki is a cracker producer and UD. Wahyu Jaya and UD. Barokah Abadi is a reseller who helps market the product. The targets of this activity are innovative products, market expansion and improving the quality of human resource management, procurement of dough mixer machines, trays, impulse sealers, nameplates, quality packaging, and SAK EMKM accounting books. The service method used is mentoring business activities in terms of production, marketing, and business financial management. The outputs resulting from this community partnership program are in the form of improving the quality of production more effectively and efficiently and hygienically with a dough mixer machine, as well as the creation of a product's unique selling point in terms of shape. Other outputs resulting from this activity are the expertise of business partners in managing production management, digital marketing, and the preparation of simple financial reports based on excel applications guided by SAK EMKM.